Hybrid Polymer Films Based Zns Nanocomposites and Its Optical and Morphological Properties: Monitoring the Role of the Binding-Site Interaction - Sanchez-Poblete, J (Elsevier Ltd, 2018)
A series of hybrid polymer films were prepared using self-assembly block copolymers as nanoreactor of ZnS nanoparticles (NPs). The self-assembled poly(acrylic acid)-block-poly(N-phenylmaleimide) was prepared by Atom-Transfer Radical Polymerization (ATRP) in different block composition. Subsequently the fluorescent NPs were synthesized into the polymer matrices in order to modify its optical and thermal properties and to analyze its effect on the morphology properties (roughness and porosity). As results, significant effects on the properties of the hybrid materials were obtained under different percentages of the NPs. These materials exhibited blue- or red-shift emission bands depending on the length of hydrophilic domain. Additionally, a quenched emission band is seen, which may also be attributed primarily to the composition of the hydrophilic domain and to the greater percentage of ZnS NPs. The hybrid polymer films showed effects on the porosity and roughness of the surfaces, which was analyzed by AFM and SEM microscopic techniques. © 2017